Qur'anic Values In The Barikan Tradition: A Study Of The Living Qur'an - M. Tamlikhan; Nabila An'imatul Maula; Ahmad Ashimulloh; Mohamad Zaenal Arifin; Fatwah Inna Aulisaina (International Journal of Religion and Social Community, 2026)
This study examines the relevance of the Barikan tradition from the perspective of the Living Qur'an, exploring how Qur'anic values are embodied in local cultural practices. The Barikan tradition represents the community's appreciation of the Qur'an through collective prayers and communal meals as expressions of gratitude, solidarity, and social harmony. This research employs a qualitative approach with a descriptive-analytical design, using observation, in-depth interviews, and literature review as data collection techniques. The findings reveal that Barikan is not merely a cultural ritual but a living manifestation of Qur'anic teachings on gratitude (Qur'an 14:7), tolerance (Qur'an 60:8), and human brotherhood (Qur'an 49:13). These values are internalized and practiced in everyday social life, reflecting the dynamic interaction between sacred text and local culture. The tradition also illustrates the Living Qur'an framework articulated by Sahiron Syamsuddin, Islah Gusmian, and Fahruddin Faiz, in which the Qur'an functions not only as a scriptural text but also as a source of lived values that shape social behavior and cultural identity. This study contributes to the Living Qur'an discourse by demonstrating that local traditions can serve as meaningful expressions of Qur'anic ethics, fostering social cohesion and embodying the universal principle of rahmatan lil-'ālamīn (mercy to all creation).